Plurality of Voices and Cultural Diversity - Laura IONICA (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
Teachers’ voice on educational-related issues seems to be the most prevalent. However, this voice is not only related to curriculum, decision-making, testing, or school management, but it comprises a complex psychological dimension with multiple reverberations on the beneficiaries of learning. In order to have a clear view on the concept of plurality of voices, it is necessary to approach it from various perspectives: pedagogical, cultural, social and psychological. Each voice provides a different communication style. The voice of the teacher is one of authority, guidance, source of inspiration, whereas the voice of the student reflects curiosity, engagement or willingness to learn. The present work aims at highlighting the impact of both teachers and students’ voice within the modern educational setting.